Pengaruh Modifikasi Alat Trehadap Keseimbangan Atlet Bola Voli Club Cenderawasih - Putra, Andika Dwi (Universitas Hamzanwadi, 2025)
This study aims to analyze the effect of changes in balance training tools on improving the balance of volleyball club cenderawasih athletes. The research method uses quantitative methods, the type of research is experimental design one group pretest and posttest this study involved 12 athletes as samples, which were selected using purposive sampling technique. Data analysis techniques using SPSS version 20 and paired sample test methods. Tool modifications include adjusting the fulcrum with 75% intensity, performed in 3 sets with a 3-5 minute rest break, and carried out three times a week for 12 sessions. The pretest results showed the majority of athletes were in the low category on the Likert scale, with scores ranging from 60 to 71. After the intervention, the posttest results showed significant improvement, with 5 athletes reaching the very high category (scores above 90) and 7 athletes in the high category (scores 80-89). No athletes remained in the low or medium categories after the intervention. Normality tests indicated that the data were normally distributed (significance value 0.44 > 0.05), and hypothesis testing with a t-statistic of 1.98 which exceeded the critical value of 1.96 at the 0.05 significance level indicated that the difference was statistically significant. It is concluded that modification of balance training equipment is an effective method to improve balance and performance of volleyball athletes.